2020
DOI: 10.21037/jgo.2019.12.05
|View full text |Cite
|
Sign up to set email alerts
|

Clinical factors associated with the development of postoperative atrial fibrillation in esophageal cancer patients receiving multimodality therapy before surgery

Abstract: Background: The incidence of esophageal cancer (EC) is increasing in the USA. Neoadjuvant therapy for locally advanced cancers followed by surgical resection is the standard of care. The most common postesophagectomy cardiac complication is atrial fibrillation (AF). New-onset postoperative AF can require a prolonged hospital stay and may confer an overall poorer prognosis. In this study, we seek to identify clinical factors associated with postoperative AF.Methods: Query of an IRB approved database of 1,039 es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…We found in the literature that in patients with EC, radiation therapy given before or after surgery increases the risk of cardiac death. For example, two studies [ 31 , 32 ] have found that after preoperative radiotherapy, there was a 36% increase in late cardiac events and a 14.9% increase in atrial fibrillation, and the risks of late cardiovascular events and atrial fibrillation correlated with age and radiotherapy dose. Another study [ 33 ] showed that postoperative radiotherapy also increased cardiovascular events in patients with EC.…”
Section: Discussionmentioning
confidence: 99%
“…We found in the literature that in patients with EC, radiation therapy given before or after surgery increases the risk of cardiac death. For example, two studies [ 31 , 32 ] have found that after preoperative radiotherapy, there was a 36% increase in late cardiac events and a 14.9% increase in atrial fibrillation, and the risks of late cardiovascular events and atrial fibrillation correlated with age and radiotherapy dose. Another study [ 33 ] showed that postoperative radiotherapy also increased cardiovascular events in patients with EC.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the risk factors of POAF following esophagectomy. [ 6 , 7 , 11 , 12 ] However, the results were inconsistent because of the different size of study population and analysis methods. A meta-analysis was conducted to investigate the risk factors and subsequent events associated with the onset of POAF following esophagectomy.…”
Section: Introductionmentioning
confidence: 99%